PROBE OF THE MAGNETIC FIELD IN THE HOT SUPERGIANT ζ Per - Butkovskaya, V. V.; Plachinda, S. I. (Одеські астрономічні публікації, 2020)
At the surface of ∼7% of single hot stars stable mainly dipolar strong magnetic fields have been detected. The main hypothesis today is that these magnetic fields are of fossil origin. In other words, these fields formed from the seed field in the molecular clouds from which the stars were formed. The recent observational and theoretical results confi- rm this theory: the properties of the observed fields correspond to those expected from fossil fields. Massi- ve stars are stars whose initial mass exceeds about 8 solar masses. Massive stars play a significant role in the chemical and dynamical evolution of galaxies. However, much of their variability, particularly during their evolved supergiant stage, is poorly understood. To date magnetic field was registered only at three hot stars of I-II luminosity types: ρ Leo (B1 Ib), ζ Ori Aa (O9.2 Ib), and ? CMa (B1.5 II). We performed high-accuracy spectropolarimetric observation of the hot supergiant ζ Per (B1 Ib) over 26 nights from 1997 to 2012 with long-slit spectrograph mounted in the coude focus of 2.6-m reflector ZTSh at the Crimean Astrophysical Observatory. We also used circularly polarized spectra obtained during 2 nights in 2008 wi- th echelle spectrograph ESPADONS mounted at 3.6- m CFHT. Effective magnetic field B e (longitudinal component of the field integrated over visible hemi- sphere) of ζ Per was calculated in the line He I 6678.149 A. Statistically significant longitudinal magnetic field (B e /σ B > 3) was registered in 14 from 199 single measurements. These significant magnetic field values are all in the range from −145 to +148 G with the mean error 27 G. We suppose the supergiant ζ Per can be magnetic, but its magnetic field properties is diffi- cult to detect likely due to the insufficient precision of the used spectropolarimetric measurements compared to the expected field strength.